Barcoding of ornamental freshwater shrimp, Neocaridina denticulata (De Haan, 1844) from the aquatic ornamental market in Purbalingga, Central Java, Indonesia - ENDANG SRIMURNI KUSMINTARSIH; HANAN HASSAN ALSHEIKH MAHMOUD; MOH. HUSEIN SASTRANEGARA; HAMDAN SYAKURI; AGUS NURYANTO; TRISNOWATI BUDI AMBARNINGRUM (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Kusmintarsih ES, Mahmoud HHA, Sastranegara MH, Syakuri H,Nuryanto A, Ambarningrum TB. 2023. Barcoding of ornamental freshwater shrimp, Neocaridina denticulata (De Haan, 1844) from the aquatic ornamental market in Purbalingga, Central Java, Indonesia. Biodiversitas 24: 3601-3608. Indonesia is one of the world’s leading aquatic ornamental shrimps producers and exports. One of the aquatic ornament shrimp species is a Neocaridina denticulate (De Haan, 1844). There is a wide range of colors including red, bright red, yellow, orange, green, blue, violet, black, and color combinations. It is a landlocked Atydiae family species comprising31 species and subspecies. Due to taxonomic difficulties, this species is continually under revision, and the validation of a few species is currently questionable and uncertain for the relationships among the various colors of N. denticulata. The Cytochrome Oxidase gene I (CO1) gene sequences of mitochondrial DNA were used for species DNA barcoding studies. This study aimed to validate the taxonomic status of different colors of N. denticulata species using the mitochondrial DNA or mtDNA Cytochrome oxidase (CO1) gene sequences. Neighbour Joining trees were constructed based on 545 bp of CO1 gene from white, black, red, yellow, blue colors, and their combination. Several sequences were derived from GenBank for relevant species from different countries and the outgroup. The result showed that all samples are homolog, even to N. denticulata from China NC_023823.1.